Evaluation of the effects of three different mouthwashes on the force decay of orthodontic chains - Maryam Omidkhoda; Roozbeh Rashed; Neda Khodarahmi (Wolters Kluwer Medknow Publications, 2015)
Background: Elastomeric chains are commonly used in orthodontics. Force decay in these materials poses clinical problems. The aim of this study was to evaluate the effects of three different mouthwashes on the force decay of orthodontic chains. Materials and Methods: In this experimental study, elastomeric chains with two different configurations were divided into eight groups (two control and six test groups). After 10 s of prestretching up to 100% of their initial length, the chains were stretched for 25 mm on jig pins and then immersed in artificial saliva, persica, chlorhexidine 0.2% and sodium fluoride 0.05% mouthwashes. Ten cycles of thermocycling between 5°C and 55°C were conducted daily during the test period. In order to reach a 200-g initial force, seven loop closed chains, and five-loop short chains were selected. Forces were recorded by digital force gauge (Lutron) at initial, 24 h, 1, 2, 3 and 4 weeks for all groups. The amount of force loss was compared among different mouthwashes and times using one-way analysis of variance (post-hoc, Tukey, α = 0.05). Results: About 20% of the force decay occurred during the first 24 h, but after that and up to the 4 th week the rate of force loss was gradual and steady. After 4 weeks, persica and chlorhexidine caused the lowest and the highest percentage of force loss, respectively. These two mouthwashes showed statistically significant differences at all points of time (P < 0.05). Conclusion: Within the limitations of this study, during the orthodontic treatment, persica is preferred to chlorhexidine for oral health control.